2020
DOI: 10.1037/edu0000425
|View full text |Cite
|
Sign up to set email alerts
|

Documenting increased participation of a student with autism in the standards for mathematical practice.

Abstract: The Common Core State Standards articulate expectations for student participation in mathematical reasoning, sense making, and discussion. Yet little to no research explores the participation of students with autism in these practices. Drawing on neurodiversity and situated sociocultural theory, this article offers a case study of the mathematics engagement of Oscar, a fifth-grade student with autism, over the duration of 1 school year. Using field notes, videotapes of classroom interactions, student work, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
6
0
2
Order By: Relevance
“…Another study that demonstrates the impact of interactive educational contexts in improving the learning of children with ASD is that carried out by Lambert et al ( 2020 ) with a fifth-grade student with autism. The authors demonstrated how, thanks to an intervention in the classroom in which the participation rules were made more explicit and additional scaffolds (such as greater responsibility of the peers and more collaborative actions) were incorporated, the child became able to explain his mathematical thinking in multiple contexts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study that demonstrates the impact of interactive educational contexts in improving the learning of children with ASD is that carried out by Lambert et al ( 2020 ) with a fifth-grade student with autism. The authors demonstrated how, thanks to an intervention in the classroom in which the participation rules were made more explicit and additional scaffolds (such as greater responsibility of the peers and more collaborative actions) were incorporated, the child became able to explain his mathematical thinking in multiple contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Although further research is needed on this aspect, the 17 selected studies shed light on the importance of implementing interaction-based learning environments. Their benefits have been evidenced for developing language, literacy, and communication skills for SEN pupils (Whalon and Hart, 2011 , among others; Chen et al, 2020 ; Ferguson et al, 2020 ), for the acquisition of mathematical competence and science learning (Lambert et al, 2020 ; Lei et al, 2020 ; Wu et al, 2020 ) and for enhancing engagement in learning (Bock, 2007 ; Carter et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Daher wird vielfach dafür plädiert, den Be griff der Neurodiversität zu verwenden (Armstrong, 2015). Der Begriff drückt aus, dass Unterschiede in kognitiven Prozessen zwischen Menschen vorteilhafte Aspekte der biologischen Diversität sind (Lambert, Sugita, Yeh, Hunt & Brophy, 2020). Um die Gefahr einer sprachlichen Stig matisierung zu reduzieren, wird in diesem Artikel eine identity-first Sprache (d. h. autistische Person) statt einer person-first Sprache (d. h. Person mit Autismus) verwendet (Gernsbacher, 2017).…”
Section: Autismusunclassified
“…. Bei der Schemainstruktion wird mit Visualisierungen mo delliert, welche Informationen in einer mathematischen Textaufgabe wichtig sind, um das zugrunde liegende ma thematische Prinzip zu erkennen, und wie auf dieserLambert et al (2020) beschreiben in ihrer Einzelfall studie ausführlich, wie Oscar, ein autistischer Junge, mit Hilfe der Lehrkraft lernte, im Sinne eines growth mindset im Mathematikunterricht Fehler als Lerngelegenheiten zu betrachten: "Usually if you get answers wrong, your brain will grow and grow." (S. 503).…”
unclassified
“…For reasoning, the articles in this special section cover the learning of: epistemic practices (Krist, 2020), argumentation structures (Nussbaum & Putney, 2020), and spatial reasoning (Ramey, Stevens, & Uttal, 2020). For participation, the articles in this collection cover: classroom participation for students with autism (Lambert, Sugita, Yeh, Hunt, & Brophy, 2020), productive classroom groupwork (Langer-Osuna, Gargroetzi, Munson, & Chavez, 2020), help-seeking and help avoidance during instructional interactions (Peeters, Robinson, & Rubie-Davies, 2020), the influence of sociopolitical context on school-based interventions (Smith & Hope, 2020), and psychological safety in direct speech acts (Woodson, 2020). Although qualitative research on these issues might exist in other venues, the aim of this special section is to put qualitative approaches, perspectives, and findings into contact with the Journal of Educational Psychology readership.…”
Section: Integrating Qualitative Research Into Psychological Publicat...mentioning
confidence: 99%